Effect of substrate moisture level on cloudberry seedling growth and development after propagation - Āboliņa, L.; Osvalde, A.; Karlsons, A. (Estonian University of Life Sciences, 2024)
Received: January 31st, 2024 Accepted: May 1st, 2024 Published: May 6th, 2024 Correspondence: laura.abolina@lu.lv Experimentation of cloudberry cultivation has recently started in Latvia. Propagation is an essential part of cloudberry cultivation strategy, and it is an important step to ensure cloudberry survival and high vitality in field conditions. Optimal moisture conditions have to be determined for seedling development in the greenhouse. Potted cloudberries, cultivar ‘Nyby’, were grown at four different relative moisture levels of the substrate (in percent of the full waterholding capacity of the peat) - 50%, 60%, 70%, and 80%. Physiological measurements were taken once every week, including the concentration of total a and b chlorophyll in SPAD units and stomatal conductance in mmol m-2s-1. Morphological parameters, such as the number of leaves per pot, leaf size (cm), number of winter buds and visual score (from 1 to 5) were measured at the end of the vegetation season. Results revealed significant differences between the substrate moisture treatments for chlorophyll content in leaves, winter bud development and visual scoring. The authors note that slightly higher results were found for all parameters for the 80% treatment, following the tendency of increased plant vitality in higher moisture levels. This study indicates that a relative moisture of at least 70% of the full water-holding capacity of the peat is necessary for successful cloudberry growth and development under greenhouse conditions.